An overview of cyber laws in Malaysia from islamic point of view - Mohd Zulkifli Muhammad; Tamrin Amboala; Siti Faeizah Mohd Ali (2011)
The paper presents a comparative study between the existing cyber laws in Malaysia and the Islamic perspective concerning four major issues in cyber space particularly concerning i. privacy, ii. trust, iii. theft and iv. contract.The study would use comparative approach from the main source of Islamic Shariah - Quran and Sunnah (tradition of the prophet s.aw.) and a thorough study of the existing law pertaining to cyber crime such as Communication and Multimedia Act 1998 and Computer Crime Act. The study prevails that the above concerns principally seems to be consistent with Islamic view. However more extensive study must be carried out when it comes to implementation of these issues in e-commerce. With more than one billion Muslim population, the research will serve as a baseline for establishing an alternative view from Islamic perspective and cyber laws that taken into account approach based on Shariah to meet new challenges for Muslim Ummah in cyberspace.